Method for preparing electromagnetic wave absorbing material and electromagnetic wave absorbing material

By acidic roasting-leaching treatment and sulfuric acid-hydrogen peroxide system treatment on the positive electrode of the waste ternary lithium battery, CoNiMn-MOF substances are formed and pyrolyzed and carbonized, the problems of metal recycling and electromagnetic pollution of waste lithium batteries are solved, and efficient recycling and utilization are achieved. Good electromagnetic wave absorption performance.

CN119464696AInactive Publication Date: 2025-02-18SHANGHAI POWER BATTERY RECYCLING CENT CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411630956.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recycle and utilize metal elements in waste ternary lithium batteries, and traditional recycling methods lead to low added value and poor economic benefits of recycling products. At the same time, electromagnetic pollution problems are becoming increasingly serious and there is a lack of effective electromagnetic wave absorbing materials.

Method used

By performing acid calcination-leaching treatment on the positive electrode of the waste ternary lithium-ion battery, lithium is recovered and the water leach slag is placed in the sulfuric acid-hydrogen peroxide system to obtain the first acid leach solution. Then, the pH value is adjusted using anhydrous sodium carbonate, sodium dicyanamide and pyrazine are added to form a CoNiMn-MOF substance, and pyrolytic carbonization is pyrolyzed under an inert atmosphere to obtain an electromagnetic wave absorbing material.

Benefits of technology

It realizes efficient recycling and utilization of the positive electrode of the used ternary lithium battery, reduces the cost of metal extraction, is simple and easy to control, and has a large and excellent preparation material. At the same time, the prepared electromagnetic wave absorbing material exhibits good absorption performance within a specific frequency range, which can effectively reduce electromagnetic pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464696A_ABST
    Figure CN119464696A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of waste lithium battery metal recovery treatment, and provides a method for preparing an electromagnetic wave absorbing material and the electromagnetic wave absorbing material.The method comprises the steps that acid roasting-leaching treatment is carried out on a positive electrode stripped from a waste ternary lithium ion battery, and water leaching liquid containing lithium salt and water leaching residues are obtained; recovering lithium based on the water immersion liquid; putting the water leaching residues into a sulfuric acid-hydrogen peroxide system to obtain a first acid leaching solution; adjusting the first acid leaching solution to a preset pH value by using anhydrous sodium carbonate to obtain a second acid leaching solution; sequentially adding sodium dicyandiamide and pyrazine into the second pickle liquor, and stirring to obtain a mixed solution; centrifugally separating the mixed solution, and collecting to obtain a CoNiMn-MOF substance; and heating the CoNiMn-MOF substance under the protection of an inert atmosphere, and performing pyrolysis and carbonization to obtain the composite material. The waste ternary lithium ion battery can be recycled to form a material without metal extraction, the metal extraction cost is reduced, the technological process is simple and easy to control, and the prepared material is large in quantity and excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of metal recovery and treatment of waste lithium batteries, and in particular to a method for preparing an electromagnetic wave absorbing material and the electromagnetic wave absorbing material. Background Art

[0002] In recent years, the new energy vehicle market has grown rapidly, promoting the widespread use of lithium-ion batteries, which has led to the accumulation of a large number of waste power lithium-ion batteries. With the advent of the retirement tide of waste lithium-ion batteries, if there are no effective recycling and treatment measures, it will cause serious environmental pollution and resource waste problems. Traditional recycling methods usually treat positive electrode materials in the form of basic raw materials, but the recycled products produced by this treatment method have low added value, resulting in poor economic benefits and is not conducive to the sustainable and healthy development of the industry. There are high-value valuable metals such as Ni, Co, and Mn in ternary lithium batteries that can be recycled, but many current studies aim to extract valuable metals from waste ternary lithium batteries for direct recycling. Directly synthesizing useful materials from waste ternary lithium battery positive electrode materials has become a hot research direction.

[0003] In the process of human progress and social development, the widespread use of electronic devices and information technology has significantly improved people's living standards and quality of life. However, this convenience has also brought new challenges, including exposure to electromagnetic waves of various frequencies and energies from electronic products and electrical equipment, resulting in electromagnetic pollution. This pollution has become a major concern in recent years, as medical evidence shows that excessive exposure to electromagnetic radiation can have adverse effects on human health. Therefore, in order to solve this problem, it is necessary to develop electromagnetic wave absorbing materials to mitigate the harmful effects of radiation in the frequency range commonly encountered in daily life.

[0004] Ideal electromagnetic wave absorbing materials should have the characteristics of light weight, high absorption capacity, wide bandwidth and thin thickness to meet the needs of different application scenarios. From the perspective of electromagnetic wave absorption mechanism, electromagnetic wave absorbing materials can generally be divided into two categories: dielectric loss materials and magnetic loss materials. Typical dielectric loss materials include carbonaceous materials, such as graphene, carbon nanotubes and carbon nanofibers. These materials show obvious advantages in low density and high stability, but their further application is limited due to the problem of impedance mismatch.

[0005] Therefore, in order to overcome the weaknesses of single-component electromagnetic wave absorbing materials, the design and configuration of multiple components has become an inevitable choice. Using metal organic framework compounds (MOFs) as precursors, the development of porous carbon-based MOFs derivatives with diverse characteristics such as controllable defects, adjustable structures, and changeable components has attracted the attention of researchers dedicated to electromagnetic wave absorption research. Compared with other absorbing materials, carbon-based MOFs derivatives have higher conductivity, which is conducive to enhancing electrical loss. By carbonizing at different temperatures, the degree of graphitization of carbon materials can be flexibly adjusted, which will further regulate electrical loss. In addition, carbon-based MOFs derivatives have outstanding high dispersibility characteristics, through which metal oxides, metal nanoparticles or other components can be highly dispersed in the carbon matrix to form a large area of ​​heterogeneous phase interface, thereby significantly improving the interface polarization loss and optimizing the impedance matching conditions.

[0006] Among the related technologies, most of them focus on how to recycle the metal elements in waste ternary lithium batteries, but there is a lack of technology to directly make synthetic materials from the metal elements in waste ternary lithium batteries. Summary of the invention

[0007] In view of the above-mentioned shortcomings of the prior art, the purpose of the present disclosure is to provide a method, device and storage medium for processing product attributes in an electronic shopping mall system to solve the problems in the related art.

[0008] The first aspect of the present disclosure provides a method for preparing an electromagnetic wave absorbing material, comprising: step S1: performing an acid roasting-leaching treatment on a positive electrode stripped from a waste ternary lithium-ion battery to obtain a water leaching solution containing lithium salt and a water leaching residue; recovering lithium based on the water leaching solution; step S2: placing the water leaching residue in a sulfuric acid-hydrogen peroxide system to obtain a first acid leaching solution; step S3: using anhydrous sodium carbonate to adjust the first acid leaching solution to a preset pH value to obtain a second acid leaching solution; step S4: adding sodium dicyanamide and pyrazine to the second acid leaching solution in sequence, stirring to obtain a mixed solution; step S5: centrifuging the mixed solution to collect a CoNiMn-MOF material; step S6: heating the CoNiMn-MOF material under the protection of an inert atmosphere and pyrolyzing and carbonizing it to obtain a composite material.

[0009] In an embodiment of the first aspect, in step S2, the concentration of sulfuric acid is 1 M, the concentration of hydrogen peroxide is 1 vol%; the temperature is 60°C~65°C or 65°C~70°C, the stirring speed is 350rpm~400rpm or 400rpm~450rpm, the solid-liquid ratio of the water-leached residue in the sulfuric acid-hydrogen peroxide system is 40g / L, and the leaching time is 1.5 hours~2 hours, 2 hours~2.5 hours or 2.5 hours~3 hours.

[0010] In an embodiment of the first aspect, in step S3, the pH value of the first acid infusion solution is adjusted to 2, and filtered to obtain a clear solution; ultrapure water is used to dilute the clear solution to 1 / 3 of the original concentration to obtain a second acid infusion solution.

[0011] In an embodiment of the first aspect, in step S4, 0.5 g of sodium dicyanamide and 0.24 g of pyrazine are added in sequence to every 50 ml of the second acid extract, and the reaction is stirred at room temperature for a preset stirring time to obtain the mixed solution; the preset stirring time is 15 minutes to 30 minutes, 30 minutes to 45 minutes or 45 minutes to 60 minutes.

[0012] In an embodiment of the first aspect, in step S5, the CoNiMn-MOF product is collected from the mixed solution separated by centrifugation, and freeze-dried for a preset freeze-drying time to obtain a CoNiMn-MOF material.

[0013] In an embodiment of the first aspect, the preset time of freeze-drying is 12 hours to 24 hours, 24 hours to 36 hours or 36 hours to 48 hours.

[0014] In the first embodiment, the inert gas in step S6 is argon.

[0015] In the first aspect embodiment, the step S6 includes: heating the CoNiMn-MOF material to 600°C at a heating rate of 2°C / min under the protection of an inert gas, maintaining a preset insulation time, pyrolyzing and carbonizing, and cooling to obtain a composite material CoNiMn@NC-600; or, heating the CoNiMn-MOF material to 700°C at a heating rate of 2°C / min under the protection of an inert gas, maintaining a preset insulation time, pyrolyzing and carbonizing, and cooling to obtain a composite material CoNiMn@NC-700; or, heating the CoNiMn-MOF material to 800°C at a heating rate of 2°C / min under the protection of an inert gas, maintaining a preset insulation time, pyrolyzing and carbonizing, and cooling to obtain a composite material CoNiMn@NC-800.

[0016] In an embodiment of the first aspect, step S1 comprises: placing the positive electrode stripped from the waste ternary lithium-ion battery in ammonium sulfate for roasting and water leaching, recovering lithium in the water leaching solution, and recovering the water leaching residue to obtain a water leaching residue solution; step S2 comprises: placing the water leaching residue solution in a sulfuric acid-hydrogen peroxide system, the sulfuric acid concentration is 1M, the hydrogen peroxide concentration is 1vol%, the temperature is 65°C, the stirring speed is 400rpm, the solid-liquid ratio is 40g / L, and the leaching time is two hours; filtering and separating the filter residue to obtain a first acid leaching solution; step S3 comprises: adjusting the pH of the first acid leaching solution to 2 using anhydrous sodium carbonate, filtering to obtain a clarified solution, and diluting the first acid leaching solution to 1 / 3 of the original concentration using ultrapure water to obtain a second acid leaching solution; step S4 comprises: For every 50 ml of the second acid leaching solution, 0.5 g of sodium dicyanamide and 0.24 g of pyrazine are added in sequence, and the mixture is stirred at room temperature for 30 min to obtain a mixed solution; the step S5 comprises: centrifuging the mixed solution, collecting the light purple CoNiMn-MOF product, washing the CoNiMn-MOF product with ultrapure water, and then drying the CoNiMn-MOF product in a freeze dryer for 24 hours to finally obtain a dark purple CoNiMn-MOF substance; the step S6 comprises: heating the CoNiMn-MOF substance to 600°C / 700°C / 800°C at a heating rate of 2°C / min under argon protection, maintaining for 3 hours, performing pyrolysis and carbonization, and cooling to obtain the composite material CoNiMn@NC-600 / 700 / 800.

[0017] The second aspect of the present disclosure provides an electromagnetic wave absorbing material, which is composed of a composite material prepared by the method for preparing an electromagnetic wave absorbing material as described in any one of the first aspects; when the electromagnetic wave frequency is 9.7 GHz and the thickness is 2.3 mm, the maximum reflection loss value of the electromagnetic wave absorbing material is -49.32 dB, and the maximum effective absorption width is 3.2 GHz.

[0018] As described above, the present disclosure relates to the technical field of metal recycling and treatment of waste lithium batteries, and provides a method for preparing an electromagnetic wave absorbing material and an electromagnetic wave absorbing material, the method comprising: performing an acid roasting-leaching treatment on the positive electrode stripped from the waste ternary lithium ion battery to obtain a water leaching solution containing lithium salts and a water leaching residue; recovering lithium based on the water leaching solution; placing the water leaching residue in a sulfuric acid-hydrogen peroxide system to obtain a first acid leaching solution; using anhydrous sodium carbonate to adjust the first acid leaching solution to a preset pH value to obtain a second acid leaching solution; adding sodium dicyanamide and pyrazine to the second acid leaching solution in sequence, stirring to obtain a mixed solution; centrifuging the mixed solution to collect and obtain a CoNiMn-MOF substance; heating the CoNiMn-MOF substance under the protection of an inert atmosphere and pyrolyzing and carbonizing it to obtain a composite material. The waste ternary lithium ion battery can be recycled and used to form materials without metal extraction, reducing the cost of extracting metals, and the process flow is simple and easy to control, and the amount of prepared materials is large and excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A schematic flow chart showing a method for preparing an electromagnetic wave absorbing material in one embodiment of the present disclosure.

[0020] Figure 2 XRD patterns showing the crystallinity of the prepared CoNiMn@NC-600, CoNiMn@NC-700, and CoNiMn@NC-800 composites.

[0021] Figure 3 SEM images of the prepared CoNiMn@NC-600, CoNiMn@NC-700, and CoNiMn@NC-800 composites are shown.

[0022] Figure 4 The elemental surface scan image of the prepared composite material CoNiMn@NC-600 is shown in the energy dispersive spectrometer (EDS).

[0023] Figure 5 A graph showing the electromagnetic wave reflection loss values ​​of the prepared CoNiMn@NC-600 composite material within a certain frequency range. DETAILED DESCRIPTION

[0024] The following is an explanation of the embodiments of the present disclosure by specific examples, and those skilled in the art can easily understand other advantages and effects of the present disclosure from the information disclosed by the present disclosure. The present disclosure can also be implemented or applied through other different specific embodiments, and the details in the present disclosure can also be modified or changed in various ways according to different viewpoints and application modules without departing from the spirit of the present disclosure. It should be noted that the embodiments in the present disclosure and the features in the embodiments can be combined with each other without conflict.

[0025] The following is a detailed description of the embodiments of the present disclosure with reference to the accompanying drawings so that those skilled in the art can easily implement the present disclosure. The present disclosure can be embodied in many different forms and is not limited to the embodiments described herein.

[0026] In the representations of the present disclosure, the reference terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" and the like mean that the specific features, structures, materials or characteristics represented in conjunction with the embodiment or example are included in at least one embodiment or example of the present disclosure. Moreover, the specific features, structures, materials or characteristics represented may be combined in any one or a group of embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples represented in the present disclosure and the features of different embodiments or examples, unless they are mutually contradictory.

[0027] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the representation of the present disclosure, "a group" means two or more, unless otherwise clearly and specifically defined.

[0028] In order to clearly describe the present disclosure, components not related to the description are omitted, and the same reference numerals are given to the same or similar components throughout the specification.

[0029] Throughout the specification, when a device is said to be "connected" to another device, this includes not only the case of "direct connection" but also the case of "indirect connection" by placing other elements therebetween. In addition, when a device is said to "include" a certain component, unless otherwise stated, it does not exclude other components, but means that other components may be included.

[0030] Although the terms first, second, etc. are used to represent various elements in this article in some examples, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element. For example, the first interface and the second interface, etc. are represented. Moreover, as used in this article, the singular forms "one", "one" and "the" are intended to also include plural forms, unless there is an opposite indication in the context. It should be further understood that the terms "comprising", "including" indicate that there are described features, steps, operations, elements, modules, projects, kinds, and / or groups, but do not exclude the existence, occurrence or addition of one or a group of other features, steps, operations, elements, modules, projects, kinds, and / or groups. The terms "or" and "and / or" used herein are interpreted as inclusive, or mean any one or any combination. Therefore, "A, B or C" or "A, B and / or C" means "any of the following: A; B; C; A and B; A and C; B and C; A, B and C". Exceptions to this definition occur only when a combination of elements, functions, steps or operations are inherently mutually exclusive in some manner.

[0031] The technical terms used herein are only used to refer to specific embodiments and are not intended to limit the present disclosure. The singular form used herein also includes the plural form as long as the sentence does not clearly indicate the opposite meaning. The meaning of "including" used in the specification is to specify specific characteristics, regions, integers, steps, operations, elements and / or components, and does not exclude the existence or addition of other characteristics, regions, integers, steps, operations, elements and / or components.

[0032] Although not defined differently, all terms, including technical and scientific terms used herein, have the same meaning as those generally understood by those skilled in the art to which the present disclosure belongs. Terms defined in commonly used dictionaries are additionally interpreted as having meanings consistent with relevant technical literature and the message of the present disclosure, and shall not be overly interpreted as ideal or very formal meanings unless defined.

[0033] The present invention will be described in detail below through specific embodiments in conjunction with the accompanying drawings.

[0034] Traditional lithium battery recycling methods usually process cathode materials in the form of basic raw materials, resulting in low added value of recycled products and poor economic benefits, which is not conducive to the sustainable and healthy development of the industry. Ternary lithium batteries contain high-value valuable metals such as Ni, Co, and Mn that can be recycled, but many current studies aim to extract valuable metals from waste ternary lithium batteries for direct recycling, while there are few studies on direct high-value recovery of metals in the form of synthetic materials. Therefore, directly synthesizing useful materials from waste ternary lithium battery cathode materials has become a hot research direction.

[0035] In addition, electromagnetic pollution has become a major concern in recent years, and electromagnetic radiation can have adverse effects on human health. Therefore, in order to solve this problem, it is necessary to develop electromagnetic wave absorbing materials to reduce the harmful effects of radiation in the frequency range often encountered in daily life.

[0036] In order to overcome the weaknesses of single-component electromagnetic wave absorbing materials, the design and configuration of multiple components has become an inevitable choice. Using metal organic framework compounds (MOFs) as precursors, the development of porous carbon-based MOFs derivatives with diverse characteristics such as controllable defects, adjustable structures, and changeable components has attracted the attention of researchers dedicated to electromagnetic wave absorption research. Compared with other absorbing materials, carbon-based MOFs derivatives have higher conductivity, which is conducive to enhancing electrical loss. By carbonizing at different temperatures, the degree of graphitization of carbon materials can be flexibly adjusted, which will further regulate electrical loss. In addition, carbon-based MOFs derivatives have outstanding high dispersibility characteristics, through which metal oxides, metal nanoparticles or other components can be highly dispersed in the carbon matrix to form a large area of ​​heterogeneous phase interface, thereby significantly improving the interface polarization loss and optimizing the impedance matching conditions.

[0037] In the related technologies, most of them are about how to recycle the metal elements in the waste ternary lithium batteries, but there is a lack of technology to directly make the metal elements in the waste ternary lithium batteries into the electromagnetic absorption material as mentioned above.

[0038] In view of this, a method for preparing an electromagnetic wave absorbing material is provided in an embodiment of the present disclosure, by which the discarded positive electrode of a ternary lithium battery can be directly processed to obtain an electromagnetic absorbing material, which is different from the low-value processing method in the related art of only recovering the metal elements in the positive electrode.

[0039] like Figure 1 As shown, a schematic diagram of the process of preparing an electromagnetic wave absorbing material in one embodiment of the present disclosure is shown.

[0040] exist Figure 1 In the method, the method comprises: Step S1: performing an acidic roasting-leaching treatment on the positive electrode stripped from the waste ternary lithium-ion battery to obtain a water leaching solution containing lithium salt and water leaching residue; and recovering lithium based on the water leaching solution.

[0041] In some embodiments, the ternary material can be a combination of three elements: nickel (Ni), cobalt (Co), and manganese (Mn), which is usually referred to as NCM in the industry. Compared with lithium cobalt oxide batteries, batteries using nickel-cobalt-manganese ternary materials as positive electrodes are safer. The positive electrode can be exemplified by NCM523, NCM811 or other NCM materials, where the numbers represent the mixing ratio of the three elements.

[0042] In some embodiments, a sulphation roasting-leaching method may be used. Sulphation roasting-leaching is to selectively convert lithium into water-soluble lithium sulfate and nickel, cobalt and manganese into water-insoluble oxides by roasting the positive electrode active material with concentrated sulfuric acid or sulfate, so that lithium is selectively separated from nickel, cobalt and manganese in the leaching stage. For example, a positive electrode powder containing lithium cobalt oxide is placed in ammonium sulfate (NH4)2SO4, roasted and water-leached, and converted into soluble lithium sulfate and cobalt sulfate, etc., and further extracted (such as filtering, purification, heating evaporation, etc.) to achieve lithium recovery.

[0043] Step S2: placing the water-leached residue into a sulfuric acid-hydrogen peroxide system to obtain a first acid leaching solution.

[0044] In some embodiments, in step S2, the sulfuric acid concentration may be 1M, the hydrogen peroxide concentration may be 1 vol%; the temperature may be 60°C to 65°C or 65°C to 70°C, preferably 65°C. The stirring speed is 350rpm to 400rpm or 400rpm to 450rpm, preferably 400rpm. The solid-liquid ratio of the water-leached residue in the sulfuric acid-hydrogen peroxide system may be 40g / L. The leaching time may be 1.5 hours to 2 hours, 2 hours to 2.5 hours, or 2.5 hours to 3 hours, preferably 2 hours.

[0045] Step S3: using anhydrous sodium carbonate to adjust the first acid leaching solution to a preset pH value to obtain a second acid leaching solution.

[0046] In some embodiments, the preset pH may be 2. Optionally, the first acid infusion solution after adding anhydrous sodium carbonate may be filtered to obtain a clear solution, and ultrapure water may be used to dilute the first acid infusion solution to 1 / 3 of the original concentration to obtain the second acid infusion solution.

[0047] Step S4: adding sodium dicyanamide and pyrazine to the second acid leaching solution in sequence, and stirring to obtain a mixed solution.

[0048] In the reaction process of step S4, CoNiMn ion is used as the central atom, sodium dicyanamide and pyrazine are used as ligands, and a complex reaction is carried out to form a metal organic framework compound.

[0049] In some embodiments, for every 50 ml of the second acid extract, 0.5 g of sodium dicyanamide (NaN(CN)2) and 0.24 g of pyrazine (C4H4N2) are added in sequence, and the reaction is stirred at room temperature for a preset stirring time to obtain the mixed solution; the preset stirring time is 15 minutes to 30 minutes, 30 minutes to 45 minutes or 45 minutes to 60 minutes, preferably 30 minutes.

[0050] Step S5: centrifugally separate the mixed solution to collect the CoNiMn-MOF material.

[0051] In step S5, the mixed solution is centrifuged to separate a lavender product, which is a CoNiMn-MOF product. The lavender product is collected and freeze-dried for a preset freeze-drying time to obtain a dark purple CoNiMn-MOF material. In some embodiments, the preset freeze-drying time is 12 hours to 24 hours, 24 hours to 36 hours, or 36 hours to 48 hours, preferably 24 hours.

[0052] Step S6: heating the CoNiMn-MOF material under the protection of an inert atmosphere and pyrolyzing and carbonizing it to obtain a composite material.

[0053] In some embodiments, the inert gas may be argon.

[0054] In some embodiments, the CoNiMn-MOF material can be heated to 600°C at a heating rate of 2°C / min under inert gas protection, maintained at a preset insulation time, pyrolyzed and carbonized, and cooled to obtain the composite material CoNiMn@NC-600.

[0055] In other embodiments, the CoNiMn-MOF material can be heated to 700° C. at a heating rate of 2° C. / min under inert gas protection, maintained for a preset insulation time, pyrolyzed and carbonized, and cooled to obtain the composite material CoNiMn@NC-700; In other embodiments, the CoNiMn-MOF material is heated to 800°C at a heating rate of 2°C / min under inert gas protection, maintained at a preset insulation time, pyrolyzed and carbonized, and cooled to obtain the composite material CoNiMn@NC-800.

[0056] Therefore, through the above method, the positive electrode of the waste ternary lithium battery can be directly processed to obtain the composite material CoNiMn@NC-600 / 700 / 800 that can constitute the electromagnetic absorption material.

[0057] based on Figure 1 , an example can be provided, wherein step S1 comprises: placing the NCM-523 positive electrode stripped from the waste ternary lithium-ion battery into ammonium sulfate for roasting and water leaching, recovering the lithium in the water leaching solution, and recovering the water leaching residue to obtain a water leaching residue solution; step S2 comprises: placing the water leaching residue solution into a sulfuric acid-hydrogen peroxide system, wherein the sulfuric acid concentration is 1M, the hydrogen peroxide concentration is 1vol%, the temperature is 65°C, the stirring speed is 400rpm, the solid-liquid ratio is 40g / L, and the leaching time is two hours; filtering and separating the filter residue to obtain a first acid leaching solution; step S3 comprises: adjusting the pH of the first acid leaching solution to 2 using anhydrous sodium carbonate, filtering to obtain a clarified solution, and diluting the first acid leaching solution to 1 / 3 of the original concentration using ultrapure water to obtain a second acid leaching solution; step S4 comprises: The second acid leaching solution is added with 0.5g of sodium dicyanamide and 0.24g of pyrazine in sequence, and the mixture is stirred at room temperature for 30min to obtain a mixed solution; the step S5 comprises: centrifuging the mixed solution, collecting a light purple CoNiMn-MOF product, washing the CoNiMn-MOF product with ultrapure water, and then drying the CoNiMn-MOF product in a freeze dryer for 24 hours to obtain a dark purple CoNiMn-MOF substance; the step S6 comprises: heating the CoNiMn-MOF substance to 600°C / 700°C / 800°C at a heating rate of 2°C / min under argon protection, maintaining the temperature for 3 hours, performing pyrolysis and carbonization, and cooling the mixture to obtain a composite material CoNiMn@NC-600 / 700 / 800, which is a new material composite of CoNiMn alloy and carbon.

[0058] Based on the inventive concept of the above method flow, the present disclosure can also provide a variety of different experimental embodiments, which are described one by one below. Example

[0059] The method flow in Example 1 comprises the following steps: (1) The waste positive electrode stripped from the battery is placed in ammonium sulfate roasting water leaching, and the Li in the NCM-523 positive electrode powder is recovered using the water leaching liquid; the water leaching residue is recovered to obtain a mixed solution A containing nickel, cobalt and manganese.

[0060] (2) Place mixed solution A into a H2SO4-H2O2 system, with H2SO4 concentration of 1M, H2O2 concentration of 1vol%, temperature of 65°C, stirring speed of 400rpm, solid-liquid ratio of 40g·L-1, and leaching time of 2h. Filter and separate the residue to obtain the first acid leaching solution; (3) adjusting the pH of the first acid leaching solution to 2 using anhydrous Na2CO3, filtering to obtain a clear solution, and then diluting the acid leaching solution to 1 / 3 of the original concentration using ultrapure water to obtain a second acid leaching solution; (4) Take 50 ml of the diluted second acid extract, add 0.5 g of sodium dicyanamide (NaN(CN)2) and 0.24 g of pyrazine (C4H4N2), and stir at room temperature for 30 min to obtain a mixed solution D; (5) The mixed solution D was centrifuged to collect the light purple product, which was washed with ultrapure water and then placed in a freeze dryer for 24 h to obtain the dark purple substance CoNiMn-MOF; (6) The dark purple material was heated to 600°C at a heating rate of 2°C / min under Ar atmosphere protection, maintained at a preset holding time, pyrolyzed and carbonized, and cooled to obtain the composite material CoNiMn@NC-600; Example

[0061] The method flow in Example 2 comprises the following steps: (1) The waste positive electrode stripped from the battery is placed in ammonium sulfate roasting and water leaching, and the Li in the NCM-523 positive electrode powder is recovered using the water leaching liquid, and then the water leaching residue is recovered to obtain a mixed solution A; (2) Place mixed solution A into a H2SO4-H2O2 system, with H2SO4 concentration of 1M, H2O2 concentration of 1vol%, temperature of 65°C, stirring speed of 400rpm, solid-liquid ratio of 40g·L-1, and leaching time of 2h. Filter and separate the residue to obtain the first acid leaching solution; (3) adjusting the pH of the first acid leaching solution to 2 using anhydrous Na2CO3, filtering to obtain a clear solution, and then diluting the acid leaching solution to 1 / 3 of the original concentration using ultrapure water to obtain a second acid leaching solution; (4) Take 50 ml of the diluted second acid extract, add 0.5 g of sodium dicyanamide (NaN(CN)2) and 0.24 g of pyrazine (C4H4N2), and stir at room temperature for 30 min to obtain a mixed solution D; (5) The mixed solution D was centrifuged to collect the light purple product, which was washed with ultrapure water and then placed in a freeze dryer for 24 h to obtain the dark purple substance CoNiMn-MOF; (6) The dark purple material was heated to 700°C at a heating rate of 2°C / min under Ar atmosphere protection, maintained at a preset holding time, pyrolyzed and carbonized, and cooled to obtain the composite material CoNiMn@NC-700; Example

[0062] The method flow in Example 2 comprises the following steps: (1) The waste positive electrode stripped from the battery is placed in ammonium sulfate roasting and water leaching, and the Li in the NCM-523 positive electrode powder is recovered using the water leaching liquid, and then the water leaching residue is recovered to obtain a mixed solution A; (2) Place mixed solution A into a H2SO4-H2O2 system, with H2SO4 concentration of 1M, H2O2 concentration of 1vol%, temperature of 65°C, stirring speed of 400rpm, solid-liquid ratio of 40g·L-1, and leaching time of 2h. Filter and separate the residue to obtain the first acid leaching solution; (3) adjusting the pH of the first acid leaching solution to 2 using anhydrous Na2CO3, filtering to obtain a clear solution, and then diluting the acid leaching solution to 1 / 3 of the original concentration using ultrapure water to obtain a second acid leaching solution; (4) Take 50 ml of the diluted second acid extract, add 0.5 g of sodium dicyanamide (NaN(CN)2) and 0.24 g of pyrazine (C4H4N2), and stir at room temperature for 30 min to obtain a mixed solution D; (5) The mixed solution D was centrifuged to collect the light purple product, which was washed with ultrapure water and then placed in a freeze dryer for 24 h to obtain the dark purple substance CoNiMn-MOF; (6) The dark purple material was heated to 800 °C at a heating rate of 2 °C / min under Ar atmosphere protection, maintained at a preset insulation time, pyrolyzed and carbonized, and cooled to obtain the composite material CoNiMn@NC-800.

[0063] Experiments on the composite material have shown that by adjusting the thickness of the material, it can achieve effective absorption in the S, C, X, and Ku bands, covering 82.1% of the 2-18 GHz frequency range. When the electromagnetic wave frequency is 9.7 GHz and the thickness is 2.3 mm, the maximum reflection loss value is as high as -49.32 dB, and the maximum effective absorption width is 3.2 GHz.

[0064] For reference Figure 2~Figure 5 , the properties of the composite materials prepared in the experimental examples are described.

[0065] Figure 2 XRD patterns showing the crystallinity of the prepared CoNiMn@NC-600, CoNiMn@NC-700, and CoNiMn@NC-800 composites.

[0066] In this XRD graph, the vertical axis is the diffraction peak intensity (Intensity), and the horizontal axis is 2θ, which is twice the diffraction angle (degree). The crystallinity is calculated by the XRD peak. Intuitively speaking, the sharper the peak, the higher the crystallinity. It can be seen that the prepared CoNiMn@NC-600, CoNiMn@NC-700, and CoNiMn@NC-800 are composite materials with high crystallinity.

[0067] Figure 3 SEM images of the prepared CoNiMn@NC-600, CoNiMn@NC-700, and CoNiMn@NC-800 composites are shown.

[0068] The main function of a scanning electron microscope (SEM) is also to magnify tiny features or objects that are too small to be seen by the human eye. SEM magnifies images by using an electron beam, rather than the light used to form images in an optical microscope. The SEM image is obtained by scanning a high-energy electron beam across the surface of the sample, hence the name scanning electron microscope (SEM).

[0069] Among them, (a) and (b) show SEM images of CoNiMn@NC-600 at different magnifications. (c) and (d) show SEM images of CoNiMn@NC-700 at different magnifications. (e) and (f) show SEM images of CoNiMn@NC-800 at different magnifications. from Figure 3 It can be seen that the prepared CoNiMn@NC-600, CoNiMn@NC-700, and CoNiMn@NC-800 have tubular distribution at a certain temperature.

[0070] Figure 4 The elemental surface scan image of the prepared composite material CoNiMn@NC-600 is shown in the energy dispersive spectrometer (EDS).

[0071] The image is collected by the spectrometer at a sampling depth of 1 micron.

[0072] Figure 4 The three areas in the upper middle layer, from left to right, show the distribution of boron fluoride (BF), carbon (C), and nitrogen (N) in the composite material. The three areas in the lower layer, from left to right, show the distribution of manganese (Mn), nickel (Ni), and cobalt (Co) in the composite material. The dots with unique colors in each area represent the corresponding elements.

[0073] according to Figure 4It can be seen that the elements in the prepared CoNiMn@NC-600 composite material are evenly distributed, and Ni, Co, and Mn elements are all present.

[0074] Figure 5 Schematic diagram of the curve showing the electromagnetic wave reflection loss value of the prepared CoNiMn@NC-600 composite material within a certain frequency range.

[0075] The thickness of the prepared CoNiMn@NC-600 composite material is 2.3 mm. Figure 5 It can be seen that the horizontal axis is the electromagnetic wave frequency (Frequency) and the vertical axis is the reflection loss (Reflection Loss). It can be seen that the composite material reaches a maximum reflection loss value of up to -49.32dB when the electromagnetic wave frequency is 9.7GHz, and has good electromagnetic wave absorption performance.

[0076] As can be seen from the above, the disclosed solution processes the positive electrode of the ternary lithium battery through a simple recycling and conversion process to obtain CoNiMn-MOF material, and obtains different synthetic materials through different heat treatments (such as 600°C, 700°C, and 800°C in Examples 1 to 3), which show relatively good performance for electromagnetic wave absorption. The recycling and conversion process is simple, and while solving the ecological and environmental pollution and electromagnetic pollution of waste ternary lithium batteries, it realizes high-value resource circulation. The process is relatively simple, the cycle is short, and the experimental process has a high repetition rate.

[0077] In summary, the present disclosure relates to the technical field of metal recycling and treatment of waste lithium batteries, and provides a method for preparing an electromagnetic wave absorbing material and an electromagnetic wave absorbing material, the method comprising: performing an acid roasting-leaching treatment on the positive electrode stripped from the waste ternary lithium ion battery to obtain a water leaching solution containing lithium salt and a water leaching residue; recovering lithium based on the water leaching solution; placing the water leaching residue in a sulfuric acid-hydrogen peroxide system to obtain a first acid leaching solution; using anhydrous sodium carbonate to adjust the first acid leaching solution to a preset pH value to obtain a second acid leaching solution; adding sodium dicyanamide and pyrazine to the second acid leaching solution in sequence, stirring to obtain a mixed solution; centrifuging the mixed solution to collect and obtain a CoNiMn-MOF substance; heating the CoNiMn-MOF substance under the protection of an inert atmosphere and pyrolyzing and carbonizing it to obtain a composite material. The waste ternary lithium ion battery can be recycled and utilized to form a material without metal extraction, reducing the cost of extracting metals, and the process flow is simple and easy to control, and the amount of prepared materials is large and excellent.

[0078] The above embodiments are merely illustrative of the principles and effects of the present disclosure, and are not intended to limit the present disclosure. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present disclosure. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed in the present disclosure shall still be covered by the protection scope of the present disclosure.

Claims

1. A method for preparing an electromagnetic wave absorbing material, characterized in that: include: Step S1: performing an acid roasting-leaching treatment on the positive electrode stripped from the waste ternary lithium-ion battery to obtain a water leaching solution containing lithium salt and water leaching residue; recovering lithium based on the water leaching solution; Step S2: placing the water-leached residue into a sulfuric acid-hydrogen peroxide system to obtain a first acid leaching solution; Step S3: adjusting the first acid leaching solution to a preset pH value using anhydrous sodium carbonate to obtain a second acid leaching solution; Step S4: adding sodium dicyanamide and pyrazine to the second acid leaching solution in sequence, and stirring to obtain a mixed solution; Step S5: centrifugally separating the mixed solution to collect the CoNiMn-MOF material; Step S6: heating the CoNiMn-MOF material under the protection of an inert atmosphere and pyrolyzing and carbonizing it to obtain a composite material.

2. The method according to claim 1, characterized in that: In step S2, the concentration of sulfuric acid is 1M, the concentration of hydrogen peroxide is 1 vol%; the temperature is 60°C~65°C or 65°C~70°C, the stirring speed is 350rpm~400rpm or 400rpm~450rpm, the solid-liquid ratio of the water-leached residue in the sulfuric acid-hydrogen peroxide system is 40g / L, and the leaching time is 1.5 hours~2 hours, 2 hours~2.5 hours or 2.5 hours~3 hours.

3. The method according to claim 1, characterized in that In step S3, the pH value of the first acid infusion solution is adjusted to 2, and filtered to obtain a clear solution; ultrapure water is used to dilute the clear solution to 1 / 3 of the original concentration to obtain a second acid infusion solution.

4. The method according to claim 1, characterized in that: In step S4, 0.5 g of sodium dicyanamide and 0.24 g of pyrazine are added in sequence to every 50 ml of the second acid extract, and the mixture is stirred at room temperature for a preset stirring time to obtain the mixed solution; the preset stirring time is 15 minutes to 30 minutes, 30 minutes to 45 minutes, or 45 minutes to 60 minutes.

5. The method according to claim 1, characterized in that In step S5, the CoNiMn-MOF product is collected from the mixed solution separated by centrifugation, and freeze-dried for a preset freeze-drying time to obtain a CoNiMn-MOF material.

6. The method according to claim 5, characterized in that The preset time of freeze drying is 12 hours to 24 hours, 24 hours to 36 hours or 36 hours to 48 hours.

7. The method according to claim 1, characterized in that The inert gas in step S6 is argon.

8. The method according to claim 1, characterized in that The step S6 comprises: The CoNiMn-MOF material was heated to 600°C at a heating rate of 2°C / min under inert gas protection, maintained for a preset insulation time, pyrolyzed and carbonized, and cooled to obtain the composite material CoNiMn@NC-600; Alternatively, the CoNiMn-MOF material is heated to 700°C at a heating rate of 2°C / min under inert gas protection, maintained for a preset insulation time, pyrolyzed and carbonized, and cooled to obtain the composite material CoNiMn@NC-700; Alternatively, the CoNiMn-MOF material is heated to 800°C at a heating rate of 2°C / min under inert gas protection, maintained for a preset insulation time, pyrolyzed and carbonized, and cooled to obtain the composite material CoNiMn@NC-800.

9. The method according to claim 1, characterized in that: The step S1 comprises: placing the positive electrode stripped from the waste ternary lithium-ion battery into ammonium sulfate for roasting and water leaching, recovering lithium in the water leaching solution, and recovering the water leaching residue to obtain a water leaching residue solution; The step S2 comprises: placing the water-leached residue solution into a sulfuric acid-hydrogen peroxide system, wherein the sulfuric acid concentration is 1M, the hydrogen peroxide concentration is 1 vol%, the temperature is 65°C, the stirring speed is 400 rpm, the solid-liquid ratio is 40 g / L, and the leaching time is two hours; filtering and separating the residue to obtain a first acid leaching solution; The step S3 comprises: adjusting the pH of the first acid leaching solution to 2 using anhydrous sodium carbonate, filtering to obtain a clarified solution, and diluting the first acid leaching solution to 1 / 3 of the original concentration using ultrapure water to obtain a second acid leaching solution; The step S4 comprises: adding 0.5 g of sodium dicyanamide and 0.24 g of pyrazine to each 50 ml of the second acid leaching solution, stirring and reacting at room temperature for 30 minutes to obtain a mixed solution; The step S5 comprises: centrifuging the mixed solution to collect a light purple CoNiMn-MOF product, washing the CoNiMn-MOF product with ultrapure water, and then drying the CoNiMn-MOF product in a freeze dryer for 24 hours to obtain a dark purple CoNiMn-MOF material; The step S6 comprises: heating the CoNiMn-MOF material to 600°C / 700°C / 800°C respectively at a heating rate of 2°C / min under argon protection, maintaining for 3 hours, performing pyrolysis and carbonization, and cooling to obtain the composite material CoNiMn@NC-600 / 700 / 800.

10. An electromagnetic wave absorbing material, characterized in that: The composite material is prepared by the method for preparing an electromagnetic wave absorbing material according to any one of claims 1 to 9; when the electromagnetic wave frequency is 9.7 GHz and the thickness is 2.3 mm, the maximum reflection loss value of the electromagnetic wave absorbing material is -49.32 dB, and the maximum effective absorption width is 3.2 GHz.

Citation Information

Patent Citations

  • Nitrogen-doped carbon nano-tube compound type catalyst encapsulated with metal cobalt nano-particles and application thereof

    CN108923051A

  • Method for preparing ternary positive electrode material through recovering waste ternary lithium battery

    CN111206148A

  • Method for preparing MOF-based nano material based on waste lithium ion battery leachate

    CN112510282A

  • Nickel-carbon composite material for absorbing electromagnetic waves and preparation method thereof

    CN115322744A

  • MOF derived carbon-based wave-absorbing material with low calcination temperature as well as preparation method and application of MOF derived carbon-based wave-absorbing material

    CN115785905A